CHARACTERISTICS OF DETECTION LINEAR POLARIZED RADARS SIGNALS - A. I. Logvin; E. A. Lutin (Научный вестник МГТУ ГА, 2016)
The article considers the characteristics of detection of linear polarized radars performance of angle orientation plane polarization radiowave.